2019
DOI: 10.1371/journal.pone.0223352
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional BLUP and single-step genomic BLUP evaluations for yearling weight and carcass traits in Hanwoo beef cattle using single trait and multi-trait models

Abstract: Hanwoo, an important indigenous and popular breed of beef cattle in Korea, shows rapid growth and has high meat quality. Its yearling weight (YW) and carcass traits (backfat thickness, carcass weight- CW, eye muscle area, and marbling score) are economically important for selection of young and proven bulls. However, measuring carcass traits is difficult and expensive, and can only be performed postmortem. Genomic selection has become an appealing procedure for genetic evaluation of these traits (by inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 43 publications
8
33
0
Order By: Relevance
“…It was clear that the inclusion of genomic information in the analysis can significantly improve prediction accuracy relative to traditional pedigree-based models due to capturing variation in Mendelian sampling [16]. The superiority of ssGBLUP over pedigree-based BLUP or GBLUP approaches for the prediction of breeding values has been reported in previous studies on Hanwoo cattle [18,26,38] and other beef cattle breeds [30,33,39]. Other studies on French dairy goats [23,40] and sheep [24] identified that ssGBLUP was more accurate than either the pedigree-based BLUP or GBLUP for milk production traits, udder type traits, and somatic cell scores.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It was clear that the inclusion of genomic information in the analysis can significantly improve prediction accuracy relative to traditional pedigree-based models due to capturing variation in Mendelian sampling [16]. The superiority of ssGBLUP over pedigree-based BLUP or GBLUP approaches for the prediction of breeding values has been reported in previous studies on Hanwoo cattle [18,26,38] and other beef cattle breeds [30,33,39]. Other studies on French dairy goats [23,40] and sheep [24] identified that ssGBLUP was more accurate than either the pedigree-based BLUP or GBLUP for milk production traits, udder type traits, and somatic cell scores.…”
Section: Discussionmentioning
confidence: 81%
“…In Hanwoo beef cattle, carcass traits (backfat thickness (BFT), carcass weight (CW), eye muscle area (EMA), and marbling score (MS)), and yearling weight (YW) are economically important traits used to select young and proven bulls [ 25 ]. Since there is enriched traditional pedigree information available in Hanwoo [ 26 ], it is expected that the use of distinct WssGBLUP alternatives [ 6 ] can be utilized to improve genomic prediction accuracy for traits with different genetic architectures [ 7 ]. Nonetheless, these methods have not yet been comprehensively investigated in breeding schemes for this breed.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 136 genes were annotated in these genomic regions for CW and, according to NCBI, some of them were associated with EMA and YW. This was expected due to the high positive genetic correlation between CW and YW (0.76) and between CW and EMA (0.56), which was estimated in Hanwoo cattle [ 31 ], indicating that the same genes were controlling these traits. The most relevant pleiotropic QTL was identified on chromosome 14 at 24.58–25.33 Mb, which explained 17.66% of additive genetic variance in CW, 7.98% in EMA, and 9.96% in YW.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 45,304 SNPs, the quality control of genomic data excluded the SNPs with an unknown position (302 SNPs) and those located on sex chromosomes (1150 SNPs). Additionally, the SNPs with call rates lower than 0.98 (2677 SNPs), minor allele frequencies lower than 0.01 (6684 SNPs), and a maximum difference between the observed and expected frequency of 0.15 as the departure of heterozygous from Hardy–Weinberg equilibrium (31 SNPs) were excluded from the analyses [ 30 , 31 ]. In the final analysis, genotypes on 34,460 SNP markers from 1540 animals (385 bulls and 1155 steers) were available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation